Generation of broadly tunable picosecond mid-infrared laser and sensitive detection of a mid-infrared signal by parametric frequency up-conversion in MgO：LiNbO_3 optical parametric amplifiers - 张秋琳 张静 邱康生 张东香 冯宝华 张景园 (Chinese physics B, 2012)
Picosecond optical parametric generation and amplification in the near-infrared region within 1.361-1.656 μm and the mid-infrared region within 2.976-4.875 μm is constructed on the basis of bulk MgO：LiNbO 3 crystals pumped at 1.064 μm.The maximum pulse energy reaches 1.3 mJ at 1.464 μm and 0.47 mJ at 3.894 μm,corresponding to a pumpto-idler photon conversion efficiency of 25%.By seeding the hard-to-measure mid-infrared radiation as the idler in the optical parametric amplification and measuring the amplified and frequency up-converted signal in the near-infrared or even visible region,one can measure very week mid-infrared radiation with ordinary detectors,which are insensitive to mid-infrared radiation,with a very high gain.A maximum gain factor of about 7 脳 10 7 is achieved at the mid-infrared wavelength of 3.374 μm and the corresponding energy detection limit is as low as about 390 aJ per pulse.